2010
DOI: 10.3928/02793695-20100701-01
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Electrotherapy Stimulation for the Treatment of Depression

Abstract: More prevalent in women than men, clinical depression affects approximately 15 million American adults in a given year. Psychopharmaceutical therapy accompanied by psychotherapy and wellness interventions (e.g., nutrition, exercise, counseling) is effective in 80% of diagnosed cases. A lesser known adjunctive therapy is that of cranial electrotherapy stimulation (CES). The major hypothesis for the use of CES in depression is that it may reset the brain to pre-stress homeostasis levels. It is conjectured that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…In pulsed CES, low-amplitude electric currents (<1 mA) are broadly applied to the brain via scalp electrodes. CES has been approved for the treatment of anxiety, depression, and insomnia by the FDA (Gilula and Barach, 2004 ; Gunther and Phillips, 2010 ; Kavirajan et al, 2014 ). CES may affect the reticular activating system, the limbic system, and the hypothalamus (Kirsch and Nichols, 2013 ).…”
Section: Adjunctive Biological Options For Treating Trd Alongside Antmentioning
confidence: 99%
“…In pulsed CES, low-amplitude electric currents (<1 mA) are broadly applied to the brain via scalp electrodes. CES has been approved for the treatment of anxiety, depression, and insomnia by the FDA (Gilula and Barach, 2004 ; Gunther and Phillips, 2010 ; Kavirajan et al, 2014 ). CES may affect the reticular activating system, the limbic system, and the hypothalamus (Kirsch and Nichols, 2013 ).…”
Section: Adjunctive Biological Options For Treating Trd Alongside Antmentioning
confidence: 99%
“…They are indicated for the treatment of anxiety, depression and insomnia. A low-intensity alternating current is transmitted across the skull for 20 minutes once or twice daily to promote alpha-wave activity and to modulate neurotransmitters, endorphins and cortisol 33 . The ive meta-analyses include 67 human studies (n = 2,910) and demonstrate the ef icacy of devices without report of adverse events 34 .…”
Section: Cranial Electrical Stimulationmentioning
confidence: 99%
“…There are currently many research studies into CES in humans (Gunther & Phillips, 2010) and so far, 29 experimental animal studies have shown mostly positive results, with several using double-blind and placebo studies. No lasting adverse effects have been reported (Fariña, 2010).…”
Section: Early Treatmentsmentioning
confidence: 99%